THE COVID-19 INFECTION FROM THE PERSPECTIVE OF THE GASTROENTEROLOGIST - Branković, Marija; Jovanović, Igor; Radonjić, Tijana; Marković, Olivera; Brajković, Milica; Popadić, Višeslav; Klašnja, Slobodan; Zdravković, Marija (Srpski medicinski časopis Lekarske komore, 2021)
The gastrointestinal tract and liver are not spared, when it comes to the coronavirus disease of 2019 (COVID-19), as it doesn’t only affect the respiratory tract, but it is also a systemic disease that causes multiple organ damage. In this review, we have united all information that is clinically significant for physicians dealing with this infection, especially for gastroenterologists. One must bear in mind that gastrointestinal symptoms can be the first and/or only indicators of COVID-19, so this infection needs to be suspected when a patient at risk presents with diarrhea, loss of appetite, abdominal pain, nausea, and/or vomiting. Upper gastrointestinal endoscopy in the COVID-19 pandemic is a major issue, as transmission of this airborne infection happens very easily during this procedure, and it should be performed only in cases of gastrointestinal emergencies. With regard to patients suffering from inflammatory bowel disease (IBD), they are often on immunosuppressive therapy, but recommendations are that no change in therapy should be made, as these patients do not fall under the category of patients who are at increased risk of contracting COVID-19. In addition, liver lesion caused by this infection develops as the result of a multifactorial mechanism and is adefinite cause for concern, especially in patients with pre-existing chronic liver conditions, who should be closely monitored.
Keywords: SARS-CoV-2; gastrointestinal tract; liver; inflammatory bowel disease; endoscopy